Régions et coopération interrégionale : dynamiques institutionnelles, de la France à l’Europe - Thomas Perrin (Territoire en Mouvement)
This article deals with the cooperation between regional authorities, or interregional cooperation and is based on the case of the French regions. The main questions are : the influence of the geographical arguments on the institutional initiatives of cooperation ; the concrete impact of these initiatives on the regional development and on the institutionalisation of new territorial forms. The article first presents the issues and characteritics of interregional cooperation and then focuses on the development of this cooperation in France, in particular through the actions of the State services. The analysis emphasizes that interregional cooperation is most of all relevant within a European framework, as shown by the numerous cooperation projects set up in the frame of euroregions, while European law provides new instruments to structure territorial cooperation organizations.